Passive targeting of ischemic-reperfused myocardium with adenosine-loaded silica nanoparticles - Galagudza, Michael (Dove Medical Press, 2012)
Pharmacological agents suggested for infarct size limitation have serious side effects when used at cardioprotective doses which hinders their translation into clinical practice. The solution to the problem might be direct delivery of cardioprotective drugs into ischemic-reperfused myocardium. In this study, we explored the potential of silica nanoparticles for passive delivery of adenosine, a prototype cardioprotective agent, into ischemic-reperfused heart tissue. In addition, the biodegradation of silica nanoparticles was studied both in vitro and in vivo. Immobilization of adenosine on the surface of silica nanoparticles resulted in enhancement of adenosine-mediated infarct size limitation in the rat model. Furthermore, the hypotensive effect of adenosine was attenuated after its adsorption on silica nanoparticles. We conclude that silica nanoparticles are biocompatible materials that might potentially be used as carriers for heart-targeted drug delivery.